Family Empowerment through Health Education as an Effort to Prevent Non-Communicable Diseases in Outpatients at Awet Muda Narmada Regional Hospital - Novita Ana Anggraini; Baiq Halimah (Institute of Advanced Knowledge and Science, 2026)
Non-communicable diseases (NCDs) remain a major cause of morbidity and mortality in Indonesia, necessitating promotive and preventive efforts involving families as key supporters in disease management. This community service activity aims to increase family knowledge and involvement in the prevention and control of NCDs through health education for outpatients at Awet Muda Narmada Regional Hospital. The activity was carried out on June 8, 2026, at the Internal Medicine Polyclinic, targeting patients and their accompanying family members during the service. The methods used included administering a pre-test, delivering material through interactive lectures, discussions, demonstrations, distributing leaflets, and evaluation using a post-test. The results of the activity showed an increase in participant knowledge regarding NCD risk factors, prevention, therapy adherence, implementing a healthy lifestyle, and self-monitoring of health conditions. Family involvement during the activity also increased understanding of their role as caregivers in supporting chronic disease management at home. In addition to providing benefits for patients and families, this activity contributed to strengthening the Hospital Health Promotion Program (PKRS) and supporting the implementation of Primary Service Integration (ILP) by utilizing service waiting time as a medium for health education. This program demonstrates that family empowerment based on health education is an effective approach to improving health literacy and is worthy of being developed as a routine program in outpatient services to support sustainable control of NCDs.